Communication technologies for vehicles : 10th International Workshop, Nets4Cars/Nets4Trains/Nets4Aircraft 2016, San Sebastián, Spain, June 6-7, 2016, Proceedings /: 10th International Workshop, Nets4Cars/Nets4Trains/Nets4Aircraft 2016, San Sebastián, Spain, June 6-7, 2016, Proceedings. (2016) - Unknown
No abstract available